(3GdWHbGJ GdSfjI aj JQGLe GdMfajIs - (3Jbj GdOjf Hf YHO GdbGOQ GdJejej GdZRj,J (B1010 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQSd QShdg HGdgOi hHYO aEf ef CQGO GdfLGI ai GdOGQjf aYdjg HShdc WQjbI ef Sda ef GdCFeI GdegJOjf CHh MfjaI GdfYeGf Gdchai s
(3BNQgG (B:s
(3BNQ GdehLhO efgG ef (B( (3aVd ajef GSeg Ydi (B) (3JQLeI (B: (3Ydi Hf eMeO Hf Ydi Hf Ndjd GdebOSi hGdTjN GdYdGeI fGUQ GdOjf GdWHdGhi s
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSN CNQi HQbe (B310 (3, (B1124 (3, (B1788 (3JGQjNs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B91s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B405 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B429 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B143 s
Keywords: (3GdJGQjNs